2021
DOI: 10.1016/j.jbc.2021.101292
|View full text |Cite
|
Sign up to set email alerts
|

The ion channel TRPM7 regulates zinc-depletion-induced MDMX degradation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…2B and E). A possible explanation was offered by the discovery [48] that MDMX interacts with TRPM7, a bi-functional cation channel protein fused with a kinase domain. TRPM7 is a master regulator of the cellular balance of divalent cations, that mediates the uptake of Zn 2+ , Mg 2+ and Ca 2+ [49], and senses oxidative stress to release Zn 2+ from intracellular vesicles [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B and E). A possible explanation was offered by the discovery [48] that MDMX interacts with TRPM7, a bi-functional cation channel protein fused with a kinase domain. TRPM7 is a master regulator of the cellular balance of divalent cations, that mediates the uptake of Zn 2+ , Mg 2+ and Ca 2+ [49], and senses oxidative stress to release Zn 2+ from intracellular vesicles [50].…”
Section: Discussionmentioning
confidence: 99%
“…TRPM7 is a master regulator of the cellular balance of divalent cations, that mediates the uptake of Zn 2+ , Mg 2+ and Ca 2+ [49], and senses oxidative stress to release Zn 2+ from intracellular vesicles [50]. TRPM7 regulates MDMX levels by modulating Zn 2+ concentration, and induces the formation of faster moving forms of MDMX on SDS-PAGE gels [48]. These forms depend on the channel function of TRPM7 and proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…A study of TRPM7 expression using Zinc (Zn) depletion induced MDMX degradation model showed the direct correlation of TRPM7 modulation and increased tumorigenesis ( Wang et al, 2021 ). Fererra and coworkers in a different study also reported the TRPM2 mediated activation of K + channels in cancer cells responsible for metastatic progression of melanoma ( Ferrera et al, 2021 ).…”
Section: Trp Channels As Potential Drug Targetsmentioning
confidence: 99%
“…For intracellular experiments, the membrane‐permeable and readily available chelator N , N , N′ , N′ ‐tetrakis(2‐pyridinylmethyl)‐1,2‐ethanediamine (TPEN) has been used to chelate mobile zinc in cells, tissues, and live animals [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Given the high affinity of TPEN for zinc(II) ions, with an apparent K d of 0.7 f m , TPEN can chelate zinc ions that are otherwise tightly bound to cellular proteins, leading to programmed cell death by apoptotic pathways [ 79 , 89 , 90 , 91 , 92 ].…”
Section: Chemical Tools To Intercept Mobile Zincmentioning
confidence: 99%